Bron : Een Artistiek Sociaal-Wetensvhappelijk Project Rond Water. - Pisters, Ine; Vandaele, John; Verstraete, Johan; Brems, Eva; Temmerman, Marleen; Pinxten, Rik; Schmidt, Peter; Tavernier, Lieven ([S.l.] : [s.n.], 2013)
Ledegen, Nicole ; Entrepot Fictief ; Sleppe / Sleppe ; Vos, Koen ; Fake, Foxx & Peggy ; Reyes, Nayra Martin ; Joosten, Diego ; Vanbeveren, Chris ; Grahovac, Goran ; Lodewijckx et al.
Bron Een Artistiek Sociaal-Wetensvhappelijk Project Rond Water, Gent 06.07.13 - 14.09.13
kunstcatalogus